The Role of Poetry in Promoting a Sustainability Mindset: Walter Benjamin as a Guide Toward a Slow Journey - Molderez, Ingrid; Baraniuk, Diana; Lambrechts, Wim (Frontiers in Sustainability, 2021)
The sustainability challenges in modern society has led to the search for more effective approaches to education for sustainable development. Research has shown that reflection leads towards more profound levels of engagement with respect to sustainable actions. Therefore, higher education has a role to play in stimulating reflection. Art-based techniques, which have not been included alongside traditional teaching methods, have begun to gain the attention in higher education as they produce a deeper impact and involvement and can have a positive influence on the minds and hearts of the students. The aim of this paper is to demonstrate that poetry can contribute to integrating the arts and humanities in management education. The potential effect of poetry on business management majors is being explored as a part of their Corporate Social Responsibility course. Poetry has considerable potential as an innovative approach to teach sustainability, but it is rather unusual in business education. Poetry was chosen as an enabler for reflection and emotions. This original teaching project was followed by a research project relying on reflective assignments. A rereading of Walter Benjamin’s Illuminations from the perspective of sustainability studies was a source of inspiration. The paper assumes that Benjamin’s ideas relate to a slow journey involving ‘awakening’, ‘wisdom’ and ‘in a process’, three elements that are at the core of promoting a sustainability mindset. The research consisted of reflection assignments students had to comply with. Their perceptions and impressions reinforce the existing knowledge about the emotional power of poetry to encourage reflection. The results show that poetry can play a relevant role in encouraging future managers to develop a frame of mind that incorporates sustainability. Business students are open to this approach because it adds a new and unexpected dimension to their studies. Despite the urge to integrate reflections, this is still an exception for the majority of management courses. The results suggest that poetry is a relevant instrument to promote a more sustainable mindset among future managers. Paradoxically, by emphasizing a slow journey, i.e. allowing time for integrating reflective practices, a transition towards sustainability in daily managerial processes can be accelerated.